Amor Mundi and Saving the Circumstance: Loving a technoscientific world according to José Ortega y Gasset and Hannah Arendt - Castleton, Alexander (Revista de Filosofía, 2022)
José Ortega y Gasset and Hannah Arendt were two thinkers influenced by the phenomenological tradition for whom worldly experiences within a specific circumstance were essential to what it means to be human. This article, first, examines their notions of ‘amor mundi’ (Arendt) and ‘salvation of circumstance’ (Ortega), pointing out their similarities concerning the individual’s relationship to the world. It then moves on to investigate some of Ortega’s and Arendt’s conceptions about science, technology, and the concomitant bureaucratization and technocratization of the world. The main thesis of this article will be that both thinkers fundamentally coincide on how the individual must relate to an increasingly scientifically and technologically-mediated world that produces isolation and mass–people.